2010
DOI: 10.1242/dmm.004440
|View full text |Cite
|
Sign up to set email alerts
|

Lkb1inactivation is sufficient to drive endometrial cancers that are aggressive yet highly responsive to mTOR inhibitor monotherapy

Abstract: SUMMARYEndometrial cancer -the most common malignancy of the female reproductive tract -arises from the specialized epithelial cells that line the inner surface of the uterus. Although significant advances have been made in our understanding of this disease in recent years, one significant limitation has been the lack of a diverse genetic toolkit for the generation of mouse models. We identified a novel endometrial-specific gene, Sprr2f, and developed a Sprr2f-Cre transgene for conditional gene targeting withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
106
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 44 publications
8
106
0
Order By: Relevance
“…As a major upstream regulator of AMPactivated protein kinase subfamily members, including MARK/Par-1, LKB1 is involved in multiple aspects of cell function and has been linked to many human diseases especially malignant tumors. [63][64][65][66][67][68][69][70][71] Recently, LKB1 has been implicated in B-cell differentiation by mediating activation-induced cytidine deaminase-dependent remodeling of immunoglobulin genes, 72 as well as in T-cell differentiation by regulating TCR-mediated activation of phospholipase C gamma1 and AMP-activated protein kinase signaling. 73,74 LKB1 is directly phosphorylated by lymphocyte-specific protein tyrosine kinase and predominantly interacts with the adaptor protein LAT as well as phospholipase C gamma1 following TCR stimulation.…”
Section: Gck-iii Kinases As Immerging Novel Immune Regulatorsmentioning
confidence: 99%
“…As a major upstream regulator of AMPactivated protein kinase subfamily members, including MARK/Par-1, LKB1 is involved in multiple aspects of cell function and has been linked to many human diseases especially malignant tumors. [63][64][65][66][67][68][69][70][71] Recently, LKB1 has been implicated in B-cell differentiation by mediating activation-induced cytidine deaminase-dependent remodeling of immunoglobulin genes, 72 as well as in T-cell differentiation by regulating TCR-mediated activation of phospholipase C gamma1 and AMP-activated protein kinase signaling. 73,74 LKB1 is directly phosphorylated by lymphocyte-specific protein tyrosine kinase and predominantly interacts with the adaptor protein LAT as well as phospholipase C gamma1 following TCR stimulation.…”
Section: Gck-iii Kinases As Immerging Novel Immune Regulatorsmentioning
confidence: 99%
“…LKB1 is an established tumor suppressor that is mutationally inactivated in a wide variety of epithelial cancers and promotes tumorigenesis when deleted in mouse models. While the underlying mechanisms for LKB1-mediated tumor suppression are not fully defined, the key role of AMPK in inactivating mTOR is thought to contribute to this process [1,2] .…”
mentioning
confidence: 99%
“…This tumor suppressive function may involve the ability of the LKB1-AMPK pathway to promote mTOR inactivation by TSC2 and raptor phosphorylation [1,2], as well as functions of other members of the family of AMPK-related kinases.…”
mentioning
confidence: 99%
“…Shackelford found that rapamycin monotherapy decreased polyp burden and size in LKB1 +/-mice with polyposis [18] . In addition, endometrial cancers with LKB1 inactivation are highly responsive to mTOR inhibitors [11] , which led us to speculate that LKB1 may be a predictor of response to rapalogs. However, in the present study, we found that NSCLC cells are insensitive to rapamycin or RAD001 by both MTS and SRB assays, and the cellular response to mTOR inhibitors has no association with LKB1 gene status.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, LKB1-inactivated endometrial cancers have been shown to be highly responsive to mTOR inhibition [11] . Therefore, LKB1 deficiency in tumors appears to be a predictive for good clinical responses to mTOR inhibitors.…”
Section: Introductionmentioning
confidence: 99%